2017
DOI: 10.3390/molecules22091456
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Formation Mechanism Investigation of Compound Precipitation from the Traditional Chinese Prescription Huang-Lian-Jie-Du-Tang by Isothermal Titration Calorimetry

Abstract: Previous studies have shown that compounds in the form of precipitate (CFP) from Huang-Lian-Jie-Du-Tang (HLJDT) were stable, and the CFP content reached 2.63% of the whole decoction and had good neuroprotective effects. However, there has been no research on their specific source. In this study, it was found that HLJDT CFP mainly came from the reaction of Scutellaria baicalensis and Coptis chinensis by studying the separated prescription components (accounting for 81.33% of HLJDT CFP). Unlike previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…This result might provide an idea to explain the combination of Scutellaria baicalensis Georgi and Coptis chinensis Franch rhizome to treat diarrhea by TCM. Finally, BA-BBR NPs showed better therapeutic effect on IBS-D than BA/BBR mixture, suggesting that the synergistic effect of BBR and BA is achieved due to the formation of self-assemblies rather than the simple mixing, which is consistent with the results of our research in vitro ( Zhang et al, 2016 ; Wang et al, 2017 ; Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result might provide an idea to explain the combination of Scutellaria baicalensis Georgi and Coptis chinensis Franch rhizome to treat diarrhea by TCM. Finally, BA-BBR NPs showed better therapeutic effect on IBS-D than BA/BBR mixture, suggesting that the synergistic effect of BBR and BA is achieved due to the formation of self-assemblies rather than the simple mixing, which is consistent with the results of our research in vitro ( Zhang et al, 2016 ; Wang et al, 2017 ; Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Inspired by the drug combination in TCM, our previous study discovered that BBR and BA could form natural self-assemblies in the form of precipitate (CFP) from Huang-Lian-Jie-Du-Tang (HLJDT). Moreover, we confirmed that BBR and BA could be self-assemble into nanoparticles in aqueous solution which induced by electrostatic interaction; and they were assembled to basic unit in a ratio of 1:1 ( Wang et al, 2017 ). Natural and low-toxicity nanomaterial for clinical use has been a hot topic ( Anastas and Eghbali, 2010 ).…”
Section: Introductionsupporting
confidence: 60%
“…During studying the effective substances of HLJDT against ischemic stroke, our team highlighted baicalin, a flavones compound isolated from HLJDT, for its beneficial effects against ischemic stroke. Consistent with the observation from other researchers [911], our previous data showed that baicalin exhibited neuroprotective effects in middle cerebral artery occlusion (MCAO) rats within a therapeutic time window of 4 h and had good antioxidative effects in vivo and in vitro [12].…”
Section: Introductionsupporting
confidence: 89%
“…In mining compatibility of TCM, self-precipitation and colloid of compounds induced by decocting has drawn a widespread attention. During the decocting of Huang-Lian-Jie-Du-Tang (HLJDT), one traditional Chinese medicinal prescription composed of Coptidis Rhizoma , Gardeniae Fructus , Radix Scutellariae , and Phellodendri Cortex in 3:3:2:2 proportions, naturally occurring precipitate were detected and identified as baicalin-berberine self-assembled complex with uniform spherical NPs microcosmically [ [84] , [85] , [86] ]. Inspired by that, two or three main bioactive compositions from TCM were integrated into a new self-assembled entity via intermolecular interactions.…”
Section: Multi-components Assembled Systems Based On Nsmsmentioning
confidence: 99%